0.8BNT–0.2BKT ferroelectric-based multimode energy harvester for self-powered body motion sensors. (May 2021) - Maria Joseph Raj, Nirmal Prashanth; Khandelwal, Gaurav; Kim, Sang-Jae
Abstract: Exploring the various modes of forces such as tensile, bending along with regular compressive force stimulation is required to achieve superior applications from piezoelectric nanogenerators (PENG). The synthesized 1-x(Bi0.5 Na0.5 TiO3 )-x(Bi0.5 K0.5 TiO3 ) (BNKT) structural analysis revealed the formation of a morphotropic phase boundary (MPB) at x = 0.2. The MPB 0.8BNT–0.2BKT system exhibited a dielectric constant of 1338 at 1 kHz, a remanent polarization (Pr ) of 37.14 μC/cm 2 with a coercive field (Ec ) of 28.8 kV/cm at 1 Hz, and a piezoelectric coefficient (d33 ) of 110 pC/N. Composite films based on BNKT82 were then used to prepare stretchable, planar, and compressive PENGs. The stretchable PENG (SPENG) generated 8.1 V and 80 nA. The planar PENG (PPENG) in bending mode yielded 12.5 V and 110 nA, while the same device in compressive mode delivered 22.5 V and 210 nA with a power density of 13.81 mW/m 2 at 90 MΩ. The PENGs analyzed under poled, unpoled, displacement, and acceleration effects systematically; also inspected stability, capacitor charging tests. The PENGs are demonstrated as self-powered human body sensors under the multimode of forces generated by the human body's movement. Graphical Abstract: ga1 Highlights: The MPB system 1-x(Bi0.5 Na0.5 TiO3 )-x(Bi0.5 K0.5 TiO3 ) used for energy conversion. The prepared ferroelectric system's structural and electrical properties were studied. The composition 0.8BNT–0.2BKT shown high Pr of 37.14 μC/cm 2 and d33 of 110 pC/N. The 0.8BNT–0.2BKT PENGs studied upon compressive, bending and stretching force. The PENGs are demonstrated as a self-powered human body motion sensor.